1999
DOI: 10.1002/hep.510290222
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase-Deficient Mice Are More Susceptible to Neutrophil–Mediated Hepatic Parenchymal Cell Injury During Endotoxemia: Importance of An Intracellular Oxidant Stress

Abstract: Neutrophils contribute to hepatocellular injury in a number of acute inflammatory reactions. However, the molecular mechanism of parenchymal cell injury remains controversial. To address the issue of whether or not reactive oxygen species (ROS) are important in the injury process, we used the galactosamine/endotoxin (Gal/ET) model of acute liver failure, which involves a neutrophilmediated parenchymal cell injury. In C3Heb/FeJ mice, Gal/ET induced a significant increase of hepatic and plasma levels of glutathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
139
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 66 publications
12
139
0
4
Order By: Relevance
“…However, the relationship between the selenium status of the host and bacterial infection has not been well investigated, although the hypothesis predicting the aggravation of disease by selenium deficiency due to impaired antioxidant defense equally applies (4). Jaeschke et al (41) reported that the application of bacterial lipopolysaccharide induced the death of GPX (-/-) mice more readily than wild-type mice, and the increased susceptibility of knock-out mice could not be modified by titrating down and up the remaining selenoproteins by selenium deprivation/ resupplementation. This study examined the effects of SelM overexpression on the composition of immune-related cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between the selenium status of the host and bacterial infection has not been well investigated, although the hypothesis predicting the aggravation of disease by selenium deficiency due to impaired antioxidant defense equally applies (4). Jaeschke et al (41) reported that the application of bacterial lipopolysaccharide induced the death of GPX (-/-) mice more readily than wild-type mice, and the increased susceptibility of knock-out mice could not be modified by titrating down and up the remaining selenoproteins by selenium deprivation/ resupplementation. This study examined the effects of SelM overexpression on the composition of immune-related cells.…”
Section: Discussionmentioning
confidence: 99%
“…By reduction of hydroperoxides to the corresponding alcohols, these enzymes can prevent the production of reactive oxygen radicals and thus may contribute to the protection of the Selenium in Biology 851 Ursini et al, 1982;Brigelius-Flohé et al, 1994 Plasma GPx (pGPx, GPx-3) Takahashi et al, 1987 Gastrointestinal GPx (GI-GPx, GPx-GI, GPx-2) Chu et al, 1993 Iodothyronine deiodinases 5Ј-deiodinase, type I (5ЈDI) Behne et al, 1990;Arthur et al, 1990 5Ј-deiodinase Lee et al, 1999;Watabe et al, 1999;Miranda-Vizuete et al, 1999;Gasdaska et al, 1999 Thioredoxin reductase homologs (SelZf1; SelZf2) Lescure et al, 1999 Selenophosphate synthetase-2 Guimaraes et al, 1996 Functionally undefined 15 kDa selenoprotein of T cells Gladyshev et al, 1998 Selenoprotein P 10 (SelP) Motsenbocker and Tappel organism's macromolecules and biomembranes against oxidation (Sies et al, 1972;Flohé, 1989;Ursini et al, 1995). The role of the cytoplasmic GPx as an 'emergency enzyme' to fight oxidative stress was verified by reverse genetics (Ho et al, 1997;Cheng et al, 1998;de Haan et al, 1998;Fu et al, 1999;Jaeschke et al, 1999) and, in this role, cGPx cannot be substituted by any of the other selenoproteins. Glutathione peroxidases, in particular the less ubiquitously distributed isozymes, are engaged in redox regulation of many metabolic processes (BrigeliusFlohé, 1999) and appear to be involved in peroxinitrite scavenging (Sies et al, 1997).…”
Section: Metabolic Function Of Mammalian Selenoproteinsmentioning
confidence: 99%
“…Apart from this hypothesis, possible clinical benefits of NACtreatment might also be due to unspecific attenuation of oxidant stress and subsequent inflammatory injury in endothelium and hepatocytes [36]. Advantages of NAC treatment could also be attributed to its vaso-relaxant properties [37], most probably via formation of S-nitrosocysteine [38].…”
Section: Discussionmentioning
confidence: 99%